Conformational SERS Classification of K‐Ras Point Mutations for Cancer Diagnostics. (12th January 2017) - Morla‐Folch, Judit; Gisbert‐Quilis, Patricia; Masetti, Matteo; Garcia‐Rico, Eduardo; Alvarez‐Puebla, Ramon A.; Guerrini, Luca
Abstract: Point mutations in Ras oncogenes are routinely screened for diagnostics and treatment of tumors (especially in colorectal cancer). Here, we develop an optical approach based on direct SERS coupled with chemometrics for the study of the specific conformations that single‐point mutations impose on a relatively large fragment of the K‐Ras gene (141 nucleobases). Results obtained offer the unambiguous classification of different mutations providing a potentially useful insight for diagnostics and treatment of cancer in a sensitive, fast, direct and inexpensive manner.